The Influence of Price, Product Quality and Sales Promotion on Consumer Buying Interest on Schneider Electric Products at PT. Kawi Agung Kencana - Ricko A.N; Johan C; Juwanto; Michel W (Jurnal Mantik, 2021)
The price of a product that is set must be in accordance with the consumer's economy, so that consumers can buy these goods. In order to meet consumer desires, companies must pay attention to the quality of their products, in order to compete with other similar company products so that consumers are interested in repeat purchases. The sales or marketing department of a company will develop promotions to inform their products so that they can influence consumers to buy them. The purpose of this study was to determine the effect of price, product quality and sales promotion on consumer buying interest in electric Schneider products at PT. Kawi Agung Kencana. The research method used is a survey approach analysis method, the type of research is quantitative descriptive, the research method is carried out by questionnaires, interviews, and documentation studies. The analytical method used is multiple linear regression. The population is customers of PT. KawiAgungKencana totaling 158 people. The sample in the study to be tested was taken from the population with the slovin formula, which amounted to 113 people. The data analysis technique used is the reliability validity test, the classical assumption test, the coefficient of determination (R2) test, multiple regression analysis, and hypothesis testing. The results of this study indicate that price, product quality and sales promotion have a simultaneous effect on buying interest. Partially, price has a significant negative effect on buying interest and product quality and sales promotions have a significant positive effect on buying interest. price, product quality and sales promotion explain their influence on buying interest at PT. KawiAgungKencana by 30.7%. while the remaining 69.3% is the influence of other variables not explained in this study.